En torno a la localización de videojuegos clásicos mediante técnicas de romhacking: particularidades, calidad y aspectos legales - Pablo Muñoz Sánchez (JoSTrans: The Journal of Specialised Translation)
The study of this paper stems from the author’s experience in the localisation of classic video games through romhacking techniques and aims at reflecting on the particularities and differences of the professional localisation of video games. Furthermore, it discusses the legality of this practice and the quality of amateur translations. Finally, the paper concludes with a reflection on the impact of amateur translations in recent times.